2007
DOI: 10.1111/j.1537-2995.2007.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of cellular products in a closed‐bag system with an incorporated dimethyl sulfoxide–resistant sterile filter outside of cleanroom facilities

Abstract: The closed system for cryopreservation of cellular products appears to be equivalent to cleanroom-based methods regarding cellular integrity and sterility when appropriate quality of sterile filters is assured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Indeed, it has been previously reported that the amount of viable transplanted CD341 cells measured after thaw does not improve prediction of engraftment kinetics compared to the total CD341 cell dose measured prefreeze. 4 Viability observed in the unselected CD451 cell population was lower compared to CD341 PBSCs, which is presumably caused by the content of granulocytes known to be highly sensitive to ex vivo apoptotic cell death as previously described. 7 However, as these cells are not critical for hematopoietic engraftment, the reduced viability of these cells may be negligible.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Indeed, it has been previously reported that the amount of viable transplanted CD341 cells measured after thaw does not improve prediction of engraftment kinetics compared to the total CD341 cell dose measured prefreeze. 4 Viability observed in the unselected CD451 cell population was lower compared to CD341 PBSCs, which is presumably caused by the content of granulocytes known to be highly sensitive to ex vivo apoptotic cell death as previously described. 7 However, as these cells are not critical for hematopoietic engraftment, the reduced viability of these cells may be negligible.…”
Section: Discussionmentioning
confidence: 69%
“…Recovery rate of CD34+ PBSC after thawing was not routinely analyzed as many factors may influence this analysis not corresponding to the direct transfer of cells from the cryobags during transplantation. Indeed, it has been previously reported that the amount of viable transplanted CD34+ cells measured after thaw does not improve prediction of engraftment kinetics compared to the total CD34+ cell dose measured prefreeze . Viability observed in the unselected CD45+ cell population was lower compared to CD34+ PBSCs, which is presumably caused by the content of granulocytes known to be highly sensitive to ex vivo apoptotic cell death as previously described .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…to Good Manufacturing Practice (GMP). Alternatively, the processing may take place in a closed system which reduces high maintenance costs of such clean rooms [24,25].…”
Section: Discussionmentioning
confidence: 99%